2022
DOI: 10.1080/1478422x.2022.2056286
|View full text |Cite
|
Sign up to set email alerts
|

Application of accelerated cyclic test with synthetic ocean water salt-deposition process to the evaluation on corrosion characteristics of weathering steel

Abstract: The corrosion of bridging structures affects their stiffness and load-carrying capacity. Hence, predicting the degree of corrosion is critical for their reliability and safety. This study examined the applicability of the newly developed accelerated corrosion test authorised by ISO 16539 Method B for evaluating the corrosion characteristics of the weathering structural steel. The non-coated weathering steel was subjected to 28, 84, and 168 days of accelerated cyclic corrosion test. The same steel material was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
(14 reference statements)
1
9
0
Order By: Relevance
“…In this study, ISO 16539 Method B was used. Our recent research 10) also confirmed that the method is a good simulation of the real corrosion en- vironment. Fig.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…In this study, ISO 16539 Method B was used. Our recent research 10) also confirmed that the method is a good simulation of the real corrosion en- vironment. Fig.…”
Section: Methodssupporting
confidence: 74%
“…The experimental data we obtained by the previous study is explained 10) . Unpainted steel plates of SM400A, SM490A, SMA400AW, and SMA490AW, were used in this research.…”
Section: Specimenmentioning
confidence: 99%
See 1 more Smart Citation
“…The first process entails exposing the specimens to a controlled environment of 35°C and 47°C salt mist for a total of 56 h following the ASTM B-117-19 standard [32]. The second method is the cyclic salt spray test, which involves three stages of testing: wetting, drying, and transition as per the study by Jiang et al [33]. Figure 6 depicts the cycle being executed.…”
Section: Coating Characterisationmentioning
confidence: 99%
“…In this section, the relationship between the spatial statistical values and the mean corrosion depth for two types of steel in differing corrosion environments was examined. According to previous studies, their relationship can be approximated by certain functions [17]. The spatial statistics values and average corrosion depths obtained from the long-duration accelerated test (168 days) might be excessively large for comparison with the atmospheric test from one year, and any model fitting for range or sill is likely to yield similar outcomes.…”
Section: Relationship Between Mean Corrosion Depth and Spatial Statis...mentioning
confidence: 99%